Chromosome disorders: the body of chromosomes - Holden, Simon (Henry Stewart Talks, 2019)
Chromosome abnormalities that can cause developmental disorders and miscarriage, How and when numerical chromosome anomalies arise during meiosis and mitosis, The inheritance of balanced chromosome translocations and inversions, How and why balanced structural chromosome rearrangements can give rise to unbalanced genomes, The clinical implications of chromosome abnormalities and their inheritance